Moderate Intensity Resistive Training Reduces Oxidative Stress and Improves Muscle Mass and Function in Older Individuals - Alessandra Vezzoli; Simona Mrakic-Sposta; Michela Montorsi; Simone Porcelli; Paola Vago; Ferdinando Cereda; Stefano Longo; Marcello Maggio; Marco Narici (Antioxidants, 2019)
An innovative moderate-intensity resistive exercise-training (RT) program was tested in thirty-five sarcopenic elders (SAR). The subjects were randomized into two groups: SAR training (SAR-RT), n = 20, 73.0 ± 5.5 years, or SAR non-training (SAR-NT), n = 15, 71.7 ± 3.4 years. The training consisted of 12-week progressive RT, thrice/week, at 60% one-repetition maximum (1RM), 3 sets, 14−16 repetitions for both upper and lower limbs. The pre and post intervention measurements included: the skeletal muscle index (SMI%); strength (1RM); stair-climbing power (SCP); muscle thickness (MT) of vastus lateralis (VL) and elbow flexors (EF), VL pennation angle (PA), rectus femoris (RF) anatomical cross-sectional area (ACSA); reactive oxygen species (ROS), total antioxidant capacity (TAC), protein carbonyls (PC), thiobarbituric acid-reactive substances (TBARS), 8-isoprostane (8-iso-PGF2-α), 8-OH-2-deoxyguanosine (8-OH-dG), as markers of oxidative stress/damage (OxS). In SAR-RT, SCP increased by 7.7% (P < 0.01), MT increased by 5.5% for VL, 10.4% for EF and PA increased by 13.4% for VL (P < 0.001 for all). The RF ACSA increased by 14.5% (P < 0.001). 1RM significantly increased by at least 67% for all muscles tested. Notably muscle strength (1RM) positively correlated (P < 0.001) with TAC and negatively with PC (P < 0.001). In conclusion, moderate intensity RT is an effective strategy to increase muscle mass and strength in SAR, while minimizing OxS.